2020
DOI: 10.1016/j.jclepro.2020.120125
|View full text |Cite
|
Sign up to set email alerts
|

Dietary recommendations in Spain –affordability and environmental sustainability?

Abstract: Global food demand is increasing due to population growth and dietary transitions, resulting from rising incomes, are associated with increased prevalence of non-communicable diseases. Improving the sustainability of the food sector is also critical for achieving the Sustainable Development Goals. This study assesses for the first time the greenhouse gases emissions (Carbon Footprint – CF), the water footprint (WF) and the cost of three omnivorous diets recommended in Spain due to their health benefits: the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 60 publications
4
42
0
Order By: Relevance
“…In addition, the Mediterranean Diet, permitting some animal food (such as diary) consumption is often advanced as a sustainable diet ( 41). Indeed, one study documented a higher GHGe (+15%) and water use (+9%) for a diet based on the Spanish dietary guidelines compared to the Mediterranean diet (González-García et al, 2020). However, it has also been reported that Mediterranean Diet had a global warming potential about twice that of the vegan diet (Castañé and Antón, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Mediterranean Diet, permitting some animal food (such as diary) consumption is often advanced as a sustainable diet ( 41). Indeed, one study documented a higher GHGe (+15%) and water use (+9%) for a diet based on the Spanish dietary guidelines compared to the Mediterranean diet (González-García et al, 2020). However, it has also been reported that Mediterranean Diet had a global warming potential about twice that of the vegan diet (Castañé and Antón, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though current societies are the most developed and informed, there is still uncertainty about what specific dietary recommendations should be followed [63]. González-García et al [64] claimed the incorporation not only of health, but also of environmental indicators, on dietary options in the Spanish national dietary guidelines, to promote their adhesion to balance and sustainable dietary habits.…”
Section: Main Finding On Sustainable Food Consumptionmentioning
confidence: 99%
“…As for the key messages clustered in the third pillar (general recommendations addressing health and sustainability), our suggestion is that they be conceived as a catchy checking list of recommended actions, such as be active, stay hydrated, drink alcohol in moderation, eat small servings, limit the consumption of ultra-processed foods, reduce sugar consumption, be flexitarian, use a shopping list, check food labels, reduce your household's food waste and loss, consider environment when cleaning, etc. Each recommended action should provide with a brief description, based on scientific evidence [46,[130][131][132][133]. In Figures 2 and 3, we suggest the appropriate description in case of few recommended actions.…”
Section: Recommendationsmentioning
confidence: 99%